2022
DOI: 10.1007/s12471-022-01716-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of mobile 6-lead electrocardiogram device for assessment of QT interval: a prospective validation study

Abstract: Introduction Ambulatory assessment of the heart rate–corrected QT interval (QTc) can be of diagnostic value, for example in patients on QTc-prolonging medication. Repeating sequential 12-lead electrocardiograms (ECGs) to monitor the QTc is cumbersome, but mobile ECG (mECG) devices can potentially solve this problem. As the accuracy of single-lead mECG devices is reportedly variable, a multilead mECG device may be more accurate. Methods This prospective dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The authors concluded that 6-lead recordings with this KardiaMobile 6L can provide high-quality ECG recordings that may be useful in clinical medicine and during clinical trials. Bergeman et al ( 18 ) studied the accuracy of the KardiaMobile 6L device for assessment of QT intervals in 234 outpatients visiting a cardiology clinic for any indication. Due to artifacts, it was impossible to perform QTc measurement in any lead in 16 mECGs (7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that 6-lead recordings with this KardiaMobile 6L can provide high-quality ECG recordings that may be useful in clinical medicine and during clinical trials. Bergeman et al ( 18 ) studied the accuracy of the KardiaMobile 6L device for assessment of QT intervals in 234 outpatients visiting a cardiology clinic for any indication. Due to artifacts, it was impossible to perform QTc measurement in any lead in 16 mECGs (7%).…”
Section: Resultsmentioning
confidence: 99%
“…KardiaMobile 6L can subsequently be connected to the corresponding application through Bluetooth on mobile devices such as tablets and smartphones to record a 30-s 6-lead mECG. It then provides an automated assessment of heart rate and heart rhythm (18). The FDA guidance allows using KardiaMobile 6L to measure QT intervals in patients with COVID-19 (19).…”
Section: Kardiamobile 6lmentioning
confidence: 99%
“…In this issue of the Netherlands Heart Journal , Bergeman and colleagues present a proof-of-concept study in 235 patients to quantify QT intervals with a 6-lead mobile electrocardiogram (mECG) device (Kardia Mobile 6L; AliveCor, Mountain View, CA, USA) [ 6 ]. For AF detection, this device is more accurate than single-lead devices [ 7 ].…”
mentioning
confidence: 99%
“…Of the 234 mECG recordings, 33 did not allow for QT determination in lead I and 31 not in lead II; neither lead was suitable in 16 patients (7%) [ 6 ]. The QT interval could not be measured from lead I or II in 43 and 3 conventional ECGs, respectively, and in neither lead in one patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation